(untitled) (Third Sector Social Economic Review, 2017)
Cooperatives are companies with variable capital that real and legal persons come together when they can not succeed on their own, and carry out in a democratic way with cooperation and mutual assistance. The cooperative system will develop within the framework that it directs the needs of consumers and society in accordance with benefits of their members and social purposes. In this context, the two concepts to be emphasized are branding and consumer-cooperative relations. Apart from the product, the concept of brand can be defined as the perception created by consumers who demand and use that product. Accordingly, consumers and brands are in an interaction that creates value for each other. Since they are trading companies, cooperatives which have entreprises producing goods or services now possess many brands. Cooperatives in the world; from agricultural production to marketing, from the bail system to insurance, from residential and workplace production to banking, embody many different sectors. Cooperatives have also made significant achievements in terms of the Turkish economy and created qualified brands. Five of them (Gübretaş, Konya Şeker, Bursa Ecza Cooperative, İzmir Ecza Kooperatifi and Trakyabirlik) are on the list of ""Top 500 Companies of Turkey"" that Fortune Magazine prepared based on the data of 2015. On the other hand, according to the survey conducted by the Istanbul Chamber of Industry on the basis of the data of 2016, five of the cooperatives and their subsidiaries (Konya Şeker, Trakyabirlik, Gübretaş, Tarım Kredi Yem San. And Marmarabirlik) take part in “Top 500 industrial Entreprise”, which has a special importance. The Association of Sugar Beet Cooperatives (PANKOBIRLIK), to which the Konya Sugar Factory, which is located at the top of both lists, has many important brands in agriculture, animal husbandry and energy, especially in food. In this study, Torku which is one of the best known among aforesaid brands and the relationship between consumer-cooperative products will be examined. In this context, it is beneffited from the results of in-depth interview made with the marketing executive of the brand.